Molecular Characterization of Trypanosoma evansi Mevalonate Kinase (TeMVK) - Duarte, Daniel P.; Ferreira, Éden R.; Lima, Fabio M.; Batista, Franciane; De Groote, Michel; Horjales, Eduardo; Miletti, Luiz C.; Bahia, Diana (Frontiers in Cellular and Infection Microbiology, 2018)
The mevalonate pathway, present in eukaryotes, archaea, and some bacteria, is an essential part of isoprenoid biosynthesis leading to production of isoprenoids, a diverse class of >30,000 biomolecules including cholesterol, heme, and all steroid hormones. Isoprenoid biosynthesis involves one of the most highly regulated enzymes in nature, 3-hydroxy-3-methylglutaryl-CoA reductase (HMGCR), which catalyzes conversion of HMG-CoA to mevalonic acid. The enzyme mevalonate kinase (MVK) subsequently converts mevalonic acid to 5-phosphomevalonic acid. Trypanosoma evansi is a flagellate protozoan parasite that causes the disease “Surra” in domesticated large mammals, with great economic impact. T. evansi has only a trypomastigote bloodstream form, and requires constant modification of the VSG (variant surface glycoprotein) coat for protection against the host immune system. We characterized the MVK of T. evansi (termed TeMVK) at molecular, biochemical, and cellular levels. TeMVK from parasite extract had molecular weight ~36 KDa, was colocalized with aldolase (a glycosomal marker enzyme) in glycosomes, and was structurally similar to Leishmania major MVK. Interestingly, the active form of TeMVK was the tetrameric oligomer form, in contrast to other MVKs in which the dimeric form is active. TeMVK was detected in parasites isolated directly from mice and was colocalized with aldolase in glycosomes. Despite lacking organized mitochondria, T. evansi synthesizes both HMGCR transcripts and protein. The mevalonate pathway also generates dolichols, which play an essential role in construction of glycosylphosphatidylinositol (GPI) anchors, and VSGs are attached to the plasma membrane via GPI anchors. MVK and HMGCR in T. evansi are therefore potentially useful targets for therapeutic drug design.